Padrões fenológicos de 111 espécies de Cerrado em condições de cultivo - Pilon, Natashi A. Lima [UNESP]; Udulutsch, Renata Giassi [UNESP]; Durigan, Giselda (Instituto de Botânica, 2015)
The knowledge on the phenological patterns for a broad group of species is an important tool to elucidate the function and structure of plant communities. Aiming to describe the phenological rhythms of Cerrado species being cultivated and to verify if they follow the patterns observed in the native communities, we recorded, every two weeks along four years, the phenology of reproductive (flowering, and fruiting) and vegetative (leaf shedding and sprouting) processes of 111 species of Cerrado in the Arboretum of Floresta Estadual de Assis, São Paulo State, Brazil. We elaborated a phenogram containing the occurrence of each phenophase in each month, for each species, as well as the frequency of these phenophases during the years of observations. We identified general patterns of fruiting, flowering and leaf dynamics for the whole set of species planted, which correspond to those found in the literature for the phenology of natural communities of Cerrado.

O conhecimento dos padrões fenológicos para um amplo grupo de espécies é importante ferramenta para elucidar o funcionamento e a estruturação de comunidades vegetais. Visando descrever os ritmos fenológicos de espécies de Cerrado e verificar se, em condições de cultivo, o conjunto de espécies segue o padrão observado para a vegetação natural, registramos quinzenalmente, durante quatro anos, a fenologia dos processos reprodutivos (floração e frutificação) e vegetativos (caducifolia e brotação) de 111 espécies de Cerrado cultivadas em arboreto na Floresta Estadual de Assis, SP, Brasil. Elaboramos um fenograma contendo a ocorrência de cada fenofase, mensalmente, para cada uma das espécies, bem como a frequência destas fenofases durante os anos de observações. Identificamos padrões gerais de sazonalidade da frutificação, floração e dinâmica foliar para o conjunto das espécies em condições de cultivo que correspondem ao encontrado na literatura para a fenologia de comunidades naturais de Cerrado.
Phenological patterns of 111 Cerrado species under cultivation
Keywords: flowering; fructification; leaf dynamics; phenology; restoration; dinâmica foliar; fenologia; floração; frutificação; restauração